Surat Edaran Menag Nomor 05 Tahun 2022 dalam Perspektif Islam Wasathiyah: Analisis Fungsi Toa, dan Pendapat Ulama - Alam An Shori (Jurnal Pemikiran Islam, 2023)
The Minister of Religious Affairs Circular Letter No. 05/2022 regarding guidelines for the use of loudspeakers in mosques and prayer rooms has attracted attention from various groups, including representatives of the people. This study aims to: (1) Understand the definition of "syiar" (Islamic propagation) and the function of loudspeakers as a means of syiar; (2) Understand the opinions of scholars in assessing the circular letter regarding the volume guidelines for loudspeakers; (3) Understand the perspective of "Wasathiyah" (moderation) in evaluating the circular letter regarding the volume guidelines for loudspeakers. The regulation of loudspeaker volume aims to create a sense of comfort for all segments of society. "Islam Wasathiyah" is considered an appropriate solution to address the challenges faced by Muslims, particularly regarding tolerance among different religious communities and within the same religious community. The research method used is descriptive qualitative with the technique of reading and note-taking as the data collection method. The main data sources include the Minister of Religious Affairs Circular Letter No. 05/2022, relevant journals, and related news articles. Data processing involves several stages, including data reduction, data presentation, and verification. The findings include: (1) "Siyar" is the activity of manifesting symbols of Islam, and loudspeakers are currently considered as instruments of syiar used for the call to prayer, "iqamah," and other religious activities. (2) Scholars from the Indonesian Council of Ulema (MUI), Nahdlatul Ulama (NU), and Muhammadiyah agree that regulating the volume of loudspeakers is crucial to create mutual comfort. (3) The Minister of Religious Affairs Circular Letter No. 05/2022 reflects the values of "Wasathiyah" in the effort to achieve consensus and diversity in the use of loudspeakers.AbstrakSurat Edaran Menag Nomor 05 Tahun 2022 tentang pedoman penggunaan pengeras suara masjid dan musala telah menuai sorotan dari berbagai kalangan, termasuk para wakil rakyat. Penelitian ini bertujuan untuk: (1) Mengetahui definisi tentang syiar dan fungsi TOA sebagai alat syiar; (2) Mengetahui pendapat para ulama dalam menilai surat edaran tentang pedoman volume pengeras suara; (3) Mengetahui perspektif wasathiyah dalam menilai surat edaran tentang pedoman volume pengeras suara. Pengaturan volume pengeras suara bertujuan untuk menciptakan rasa nyaman bagi semua kalangan. Islam Wasathiyah dipandang sebagai solusi yang tepat dalam menyelesaikan permasalahan umat Islam terkait toleransi antar umat beragama dan seagama. Metode yang digunakan adalah deskriptif kualitatif dengan teknik baca dan catat sebagai teknik pengumpulan data. Sumber data utama adalah Surat Edaran Menag Nomor 05 Tahun 2022, jurnal-jurnal sebagai kajian terdahulu, dan berita-berita terkait. Pengolahan data dilakukan melalui tahap reduksi data, penyajian data, dan verifikasi. Adapun hasil antara lain (1) Syiar merupakan kegiatan menampakkan simbol-simbol agama Islam, sedangkan TOA saat ini dianggap sebagai alat syiar yang digunakan untuk azan, iqamah, dan kegiatan keagamaan lainnya. (2) Para ulama dari MUI, NU, dan Muhammadiyah sepakat bahwa pengaturan volume pengeras suara sangat penting untuk menciptakan kenyamanan bersama. (3) Surat Edaran Menag Nomor 05 Tahun 2022 mencerminkan nilai-nilai wasathiyah dalam upaya mencapai kesepakatan dan keberagaman penggunaan pengeras suara.